Articular Cartilage Gene Expression after Coxofemoral Joint Luxation in the Dog - Korakot Nganvongpanit; Waranee Pradit; Siriwadee Chomdej (Veterinary Medicine International)
This study examined the relationship between days of hip luxation and the expression of various mRNA. Twenty-six articular cartilages were used in the experiment: 3 samples were from normal dogs and 23 samples were collected from the femoral heads of hips that had been luxated for different lengths of time. Ten mRNA, including nonapoptotic genes (AGG, COL2A1, MMP-3, HAS-1, HAS-2, and TIMP-1) and apoptotic genes (BAX, BCL-2, CAS-3, and CAS-9), were studied for their expression using real-time PCR. We found very high correlation between expression level and luxation days (r2>0.9) in COL2A1, MMP-3, HAS-1, HAS-2, TIMP-1, BAX, and CAS-9, while the others (AGG, BCL-2, and CAS-3) also showed high correlation (r2=7–9). And we found a significant difference (P<0.05) in the expression of transcripts depending on the number of luxation days. In conclusion, a delay in joint reduction may increase the chances of development of osteoarthritis.